CONTENT OF INTERNATIONAL EDUCATION OF STUDENTS - Zheyuan, Wei (Continuing Professional Education: Theory and Practice, 2019)
The article analyzes the concept of "multicultural education", "intercultural education" in the works of Ukrainian researchers. The main aim of intercultural education is the need to make society open to other cultures, to ensure the peaceful coexistence of peoples. In today's globalized world intercultural education contributes to the European integration, and helps maintain social peace in the midst of multi-ethnic society. Overcoming negative stereotypes is important to understand our own "cultural memory of the nation", which carries information about the culture of our people and respect the cultural heritage of the neighboring peoples from generation to generation. The author consideres the separation of these concepts in content. The composition of intercultural education (intercultural communication, intercultural tolerance, intercultural identity) and its content is determined. It is concluded that intercultural education students aimed at developing an attitude of respect to the other, people of different ethnic backgrounds with a different way of thinking and cultural values of different nations, cultures interoperability with knowledge of the importance of our own culture and our own identity.